Multiple reaction monitoring mass spectrometry for the discovery of environmentally modulated proteins in an aquatic invertebrate sentinel species, Gammarus fossarum. (15th December 2022) - Leprêtre, Maxime; Geffard, Olivier; Espeyte, Anabelle; Faugere, Julien; Ayciriex, Sophie; Salvador, Arnaud; Delorme, Nicolas; Chaumot, Arnaud; Degli-Esposti, Davide
Abstract: Multiple reaction monitoring (MRM) mass spectrometry is emerging as a relevant tool for measuring customized molecular markers in freshwater sentinel species. While this technique is typically used for the validation of protein molecular markers preselected from shotgun experiments, recent gains of MRM multiplexing capacity offer new possibilities to conduct large-scale screening of animal proteomes. By combining the strength of active biomonitoring strategies and MRM technologies, this study aims to propose a new strategy for the discovery of candidate proteins that respond to environmental variability. For this purpose, 249 peptides derived from 147 proteins were monitored by MRM in 273 male gammarids caged in 56 environmental sites, representative of the diversity of French water bodies. A methodology is here proposed to identify a set of customized housekeeping peptides (HKPs) used to correct analytical batch effects and allow proper comparison of peptide levels in gammarids. A comparative analysis performed on HKPs-normalized data resulted in the identification of peptides highly modulated in the environment and derived from proteins likely involved in the environmental stress response. Overall, this study proposes a breakthrough approach to screen and identify potential proteins responding to relevant environmental conditions in sentinel species. Graphical abstract: Image 1 Highlights: Dynamic MRM proteomic profiles of caged gammarids in 56 French river sites. Discovery of customized housekeeping peptides for correcting batch effects Identification of highly modulated proteins in the environment Novel strategy for the discovery of environmental biomarkers